Good Practice Issues in Working with Interpreters in Mental Health - MORRISSEY, JEAN (My University, 2004)
If access to appropriate mental health services is not to be limited to people’s ability to speak a dominant or host language used by mental health providers, an interpreter or bicultural worker will be required. This article makes suggestions for good practice in working with interpreters either in situations of ongoing-armed conflict or with asylum seekers refugees and internally displaced people who have fled from areas of armed conflict.
PUBLISHED
Keywords: Mental Health